An Editorial on the Special Issue “Where Are We Now and Where Is Cell Therapy Headed?” - Andrea Papait; Paola Chiodelli (Pharmaceutics, 2025)
Cell-based therapies have swiftly transitioned from experimental modalities to core components of modern translational medicine [...]